Attitudes towards European financial solidarity during the Covid-19 pandemic: evidence from a net-contributor country. (19th February 2021) - Bobzien, Licia; Kalleitner, Fabian
ABSTRACT: Whilst the Covid-19 pandemic affects all European countries, the ways in which these countries are prepared for the health and subsequent economic crisis varies considerably. Financial solidarity within the European Union (EU) could mitigate some of these inequalities but depends upon the support of the citizens of individual member states for such policies. This paper studies attitudes of the Austrian population – a net-contributor to the European budget – towards financial solidarity using two waves of the Austrian Corona Panel Project collected in May and June 2020. We find that individuals (i) who are less likely to consider the Covid-19 pandemic as a national economic threat, (ii) who believe that Austria benefits from supporting other countries, and (iii) who prefer the crisis to be organized more centrally at EU-level show higher support for European financial solidarity. Using fixed effects models, we further show that perceiving economic threats and preferring central crisis management also explain attitude dynamics within individuals over time. We conclude that cost–benefit perceptions are important determinants for individual support of European financial solidarity during the Covid-19 pandemic.